2005
DOI: 10.1088/0953-2048/18/9/017
|View full text |Cite
|
Sign up to set email alerts
|

Growth and superconducting properties of (Eu,R)Ba2Cu3O7−δ(R = Er, Tm) single-crystalline whiskers

Abstract: We have grown single-crystalline whiskers of superconducting (Eu, R)-123 (R = Er, Tm), systematically changing the ionic radius by means of doping with Er or Tm, which have smaller ionic radii, in place of Eu. We tried to gain an understanding of the oxidation, doping and superconducting state of the materials by annealing whiskers at different conditions, studying the temperature dependence of the magnetization and carrying out x-ray diffraction analysis and quantitative electron probe microanalysis measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The cause of the lower T c of the Gd-123 whiskers is the substitution of Gd 3+ ions for the Ba 2+ sites in Gd-123 whiskers and the oxygen deficiency in Gd-123 as-grown whiskers. It was reported that the T c of Ca-containing R-123 as-grown whiskers was markedly increased to about 80 K by annealing in oxygen 6,14) . Therefore, the lower T c of the Gd-123 as-grown whiskers is mainly due to the oxygen deficiency in Gd-123.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cause of the lower T c of the Gd-123 whiskers is the substitution of Gd 3+ ions for the Ba 2+ sites in Gd-123 whiskers and the oxygen deficiency in Gd-123 as-grown whiskers. It was reported that the T c of Ca-containing R-123 as-grown whiskers was markedly increased to about 80 K by annealing in oxygen 6,14) . Therefore, the lower T c of the Gd-123 as-grown whiskers is mainly due to the oxygen deficiency in Gd-123.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that the T c of Ca-containing R-123 as-grown whiskers was markedly increased to about 80 K by annealing in oxygen. 6,14) Therefore, the lower T c of the Gd-123 as-grown whiskers is mainly due to the oxygen Table I. Lengths of whiskers grown under optimum growth conditions, such as nominal compositions of precursors, heat treatment temperature (T max ), holding time at T max (t max ), and rate of cooling to 900 C (C R ).…”
Section: Resultsmentioning
confidence: 99%
“…In the case of the high temperature superconducting single crystal whiskers, the Bi-Sr-Ca-Cu-O system is most popular, probably due to relatively easy fabrication [17,[24][25][26][27]. The whiskers were also observed in RBa 2 Cu 3 O 7+x systems with R = rare earth elements [17,28,29], whereas little is known about whisker growth and their properties in the Tl-and Hg-based superconductors [30]. For the case of Bi2212 and Bi2223 cuprate superconductors various mechanisms were proposed, as summarized in review by Badica et al [27].…”
Section: Resultsmentioning
confidence: 99%
“…[3][4][5] Many attempts have been done to fabricate single crystal superconducting whiskers using different superconducting systems and techniques. Pure and Al, Ag, Er, Pb, La, Te, Ga, Ge, K, Na, Co, Fe, Zn and Li doped Bi-2212, [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] pure yttrium barium copper oxide (YBCO), [21][22][23] a series of RBa 2 Cu 3 O x (R5Sm, Eu, La, Nd, Tm, Yb, Lu, Ho, Dy and Gd), 24,25 Ca and Te doped EuBa 2 Cu 3 O x 26 and MgB 2 27 are only some of the examples for such studies.…”
Section: Introductionmentioning
confidence: 99%